Social Support, Socio Demographic Factors and Elder Abuse: A Quantitative Study - Mobolaji Grace Olasupo; Mathew Olugbenga Olasupo; Dare Azeez Fagbenro (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2020)
Elder abuse has continued to be a serious concern to many stakeholders in the world and Nigeria as reported by researchers, as well as various media platforms. It is from this fact that this present study examined the role of social support and socio demographic factors on elder abuse in Ile-Ife Osun state, Nigeria. Theory of social exchange provided the theoretical framework while a descriptive survey was adopted. Three hundred and ninety-two (392) respondents (Males = 192, Females = 200, M = 70.77, S.D. = 6.33) were selected using a purposive sampling technique. Data were collected using a structured questionnaire comprising demographics variables, elder abuse scale (α = .65), and social support scale (α = .94). Data were analysed using T-test for independence measure and analysis of variance (ANOVA). T-test for independent statistics revealed that social support differentiated the experienced elder abuse t(390) = -3.33; p < .001). There were some gender differences in elder abuse (t(390) = 2.20; p = .028). There was no significant relationship between socioeconomic status and elder abuse (F(3, 389) = 1.46; p = .225). The study concluded that social support and gender played a vital role with elder abuse in Osun state. The study, therefore, recommended that government should provide appropriate social support such as prompt payment of pension and gratuity, provision of feeding, good, as well as living arrangements with special attention on elderly men